Kaji Eksperimental Torsi Statik Dan Torsi Dinamik Hidrokinetik Turbin Savonius Type Bach Tiga Sudu Besar Dengan Tambahan Tiga Sudu Kecil - Seprinaldo Seprinaldo; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The savonius turbine is a vertical axis wind turbine that can be used in low speed waters. The compounding is to make a six-blade savonius type bach with three large blades plus three small blades where the small blade is 2/3 of the length of the large blade with hydrokinetic driving force. Variation of the water velocity is 0.34 m / s and 0.59 m / s. This study the shape and dimensions of the turbines used are the height of the 300 mm turbine, the diameter of the turbine is 330 mm, the length of the blade is 150 mm and the length of the blade is 100 mm. In this study the data collection process using pulley as a conductor of power which is given a load to calculate the load that can be taken by the turbine and above the pulley is given as a pointer to measure static load. The purpose of this study was to determine how much the static and dynamic torque of a six-blade bach type savonius turbine with three large blades and three small blades.Keywords: Turbine savonius, large blade, small blade, hydrokinetic